Flödesbalans för förädlingsverken i Svappavaara - Hagemalm, Jenny (2012)
LKAB has a goal to increase the production of iron ore products to 37 million tonnes by the year 2015. It is planned to open three new mines in the vicinity of Svappavaara and they will provide the processing plant in Svappavaara with ore. The processing plant is currently provided with ore from the mine in Kiruna. It is of interest to clarify the process in terms of water- and material flows with the current circumstances. The profit from this is that references will be available when the processing plant in Svappavaara receives other types of ores than today. The purpose of this study was to make a flow balance over the production in Svappavaara and analyze how the current process is running. Energy and iron losses were identified and the possibility of recycling water and waste-material from the pelletizing plant were studied. Two sampling campaigns in the plants were done to obtain sufficient process information for the construction of the flow balance. Assay results combined with data from automatic measurements in the process were used with the software Algosys Bilmat to perform balance calculations. The balance is based on results from sampling 1, but results from sampling 2 were used for comparison and verification. Sampling 2 was two weeks later, but its results were generally very similar to the results from sampling 1. It is therefore concluded that the process in Svappavaara was stable during the samplings. However, it was not possible to include phosphorus removal by flotation in the balance since it was not running during samplings. It was found that waste from the primary magnetic separation contained more iron than preferred and approximately 7 % consisted of magnetite. The high iron content in the waste from the secondary magnetic separation is explained by the fact that most of this iron is in the form of hematite. Losses of magnetite to the primary waste can be caused by too high water addition. Another reason might be that the magnetite is in such small particles that they don’t have ...